Failure to Meet Due Date of Delivery to Customer - Bahari, Siti Fathiyah Hanim (1998)
Percetakan Nasional Malaysia Berhad (PNMB), previously it was a government body but since 6 years ago has been corporatized. It has been operating to cater all sort of customers which offer product that make to order as well as make to stock. PNMB goal is to penetrate commercial market domestically and internationally but however there is a big problem that need to be solve first as to avoid repetitive result. The problem is PNMB fail to deliver goods on time to their customers. With this study will help to analyze the factors affecting to the problems as well as forecast some solution as to solve it. All the methods can easily to be implemented and appropriate for PNMB plant. Hence, let's us discussed and analyze the issues in more details.